PENGARUH PERGANTIAN MANAJEMEN, OPINI AUDIT, UKURAN KAP DAN OPINI AUDIT GOING CONCERN TERHADAP AUDITOR SWITCHING (Studi Pada Perusahaan Perbankan di Bursa Efek Indonesia Tahun 2009– 2014) - Syafrul Antoni; Wirmie Eka Putra; Rahayu Rahayu (Jurnal Ilmu Akuntansi, 2018)
The purpose of this study is to examine the factors that influence the turnover of publicaccounting firms (KAP). These factors are management change, audit opinion, hoodsize and going-concern audit opinion. This topic was chosen because the issue ofauditor independence regarding the length of the engagement period is still relevant inthe business world, besides the Government of the Republic of Indonesia through theMinister of Finance Decree No. 423 / KMK.06 / 2002 concerning Public AccountantServices regulates the limitation of the period of KAP engagement, so that it thenimpacts on the replacement of KAP.This study analyzes the impact of the independent variables on the replacement ofKAP using logistic regression analysis. The object of research is a company listed onthe Indonesia Stock Exchange in 2009-2014. Samples are selected by purposivemethod with a focus on banking companies. The type of data in this study isdocumentary data obtained from ICMD 2009-2014, as well as published audited annualfinancial reports.Tests on 78 samples of financial companies listed on the IDX during 2009-2014 statedthat changes in KAP were related and influenced by audit opinion. The other variablesin this study did not significantly influence.